2016
DOI: 10.1039/c5cp06630a
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the interplay between hydrogen bonding and rotational energy barrier to fine-tune the properties of triazine molecular glasses

Abstract: Mexylaminotriazine derivatives form molecular glasses with outstanding glass-forming ability (GFA), high resistance to crystallization (glass kinetic stability, GS), and a glass transition temperature (Tg) above room temperature that can be conveniently modulated by selection of the headgroup and ancillary groups. A common feature of all these compounds is their secondary amino linkers, suggesting that they play a critical role in their GFA and GS for reasons that remain unclear because they can simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 53 publications
0
56
0
Order By: Relevance
“…With the aim of applying an estimative approach to measure the hydrogenb ond strength, the rotational energy profile of the dihedralangle between the hydrazone moiety and the pyridine ring was calculated at the DFT/B3LYP/6-311 + G(d,p) level of theory as the relationship between both parameters was previously described (Figure 9). [57] As observedi nF igure 9, the dihedral angle rotational profile exhibits inflexion points at approximately 0, 100, 130, À100, and À1308.I nflexion at 08 corresponds to the globalm inima for both isomers where the conformationa llows the maximum possible NÀH···N interaction. Although IUPAC defines the rotational barriera st he energy barrierb etween two adjacent minimap oints, ar otation about C11ÀC12 from À1308 or 1308 to 08 must overcomealocal maximum at 908,i ncreasing the energy barriera nd, consequently,h as ar otational barrier that corresponds to the NÀH···N interaction equal to 11.29 and 11.03 kcal mol À1 for 1-E,Z and 1-Z,Z,r espectively.…”
Section: Hydrogen Bond Energy Estimation By Rotational Barrier Calculmentioning
confidence: 59%
See 1 more Smart Citation
“…With the aim of applying an estimative approach to measure the hydrogenb ond strength, the rotational energy profile of the dihedralangle between the hydrazone moiety and the pyridine ring was calculated at the DFT/B3LYP/6-311 + G(d,p) level of theory as the relationship between both parameters was previously described (Figure 9). [57] As observedi nF igure 9, the dihedral angle rotational profile exhibits inflexion points at approximately 0, 100, 130, À100, and À1308.I nflexion at 08 corresponds to the globalm inima for both isomers where the conformationa llows the maximum possible NÀH···N interaction. Although IUPAC defines the rotational barriera st he energy barrierb etween two adjacent minimap oints, ar otation about C11ÀC12 from À1308 or 1308 to 08 must overcomealocal maximum at 908,i ncreasing the energy barriera nd, consequently,h as ar otational barrier that corresponds to the NÀH···N interaction equal to 11.29 and 11.03 kcal mol À1 for 1-E,Z and 1-Z,Z,r espectively.…”
Section: Hydrogen Bond Energy Estimation By Rotational Barrier Calculmentioning
confidence: 59%
“…With the aim of applying an estimative approach to measure the hydrogen bond strength, the rotational energy profile of the dihedral angle between the hydrazone moiety and the pyridine ring was calculated at the DFT/B3LYP/6–311+G(d,p) level of theory as the relationship between both parameters was previously described (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…This ∼10 cm −1 energy difference between the CO stretching of P1‐X and P2 is indicative of the formation of regular well‐ordered hydrogen bonding network in the P1‐X state . Two new signals centered at 3435 cm −1 and 3258 cm −1 in the P1‐X state correspond to vibration of free and hydrogen bonded NH of the sym ‐triazine, respectively . Analysis of the infrared absorption profile of the P1‐M state showed non‐ordered urethane and sym ‐triazine hydrogen bonding motifs as well as a significant contribution of free urethane fragments (1738 cm −1 CO vibration).…”
Section: Resultsmentioning
confidence: 97%
“…The difference in behavior observed with respect to polymers could be due to the absence of chain entanglement, as well as the presence of hydrogen bonds between molecules, even at temperatures above Tg, that result in differences in diffusion rates under different environments. For example, it has been demonstrated that the degree of hydrogen bonding in mexylaminotriazine glasses decreases as a function of temperature, 37 while the chain entanglement of polymers is only weakly dependent on temperature.…”
Section: Resultsmentioning
confidence: 99%